2004
DOI: 10.1128/jvi.78.14.7610-7618.2004
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulant Patch Enhances Immune Responses to Influenza Virus Vaccine in Aged Mice

Abstract: Improvement in the immune response to influenza virus vaccination in the elderly represents the primary unmet need in influenza virus vaccination. We have shown that topical application of immunostimulating (IS) patches containing heat-labile enterotoxin of Escherichia coli (LT) enhances immune responses to injected vaccines. We extend these findings and show that LT-IS patch application enhances the antibody responses to influenza virus vaccination in both young and aged mice. LT-IS patches markedly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…The structural and immune properties of the skin enable a split adjuvant and antigen vaccination strategy: GuebreXabier et al first demonstrated that topical administration of an enterotoxin improved the amplitude of the antibody response to intramuscular or subcutaneous influenza virus antigen in mice (36). This group also showed that an enterotoxin-containing patch could induce a trend toward higher antibody responses to influenza vaccination in the elderly (37), demonstrating the relevance of this approach in humans.…”
Section: Discussionmentioning
confidence: 97%
“…The structural and immune properties of the skin enable a split adjuvant and antigen vaccination strategy: GuebreXabier et al first demonstrated that topical administration of an enterotoxin improved the amplitude of the antibody response to intramuscular or subcutaneous influenza virus antigen in mice (36). This group also showed that an enterotoxin-containing patch could induce a trend toward higher antibody responses to influenza vaccination in the elderly (37), demonstrating the relevance of this approach in humans.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, intraperitoneal injection of either Freund's complete adjuvant (FCA) or live T. pyriformis upregulated multiple AMPs expression in channel catfish skin and total antibacterial activity peak on day seven following injection [189]. The mechanism(s) involved by which these AMPs may have enhanced expression at sites distal from the location of immunostimulant administration is unknown, but might be analogous to that observed when immunostimulants are administered to the skin and result in enhanced protection against infection at distal sites [190]. One possibility may imply the Langerhans cells.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…Physical and chemical penetration enhancement techniques that disrupt the integrity of the SC have also been described (Chen et al 2001;Glenn and Alving 1999a;Glenn et al 2003;Guebre-Xabier et al 2004;Mikszta et al 2002). We have tested concepts with clinical relevance to patch delivery in model systems and subsequently applied them to human skin where penetration enhancement appears to represent an improvement over simple hydration of the skin.…”
Section: Tci Techniquesmentioning
confidence: 94%